1961
DOI: 10.1139/o61-081
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine Metabolism of a Sympathetic Ganglion

Abstract: The synthesis, storage, and release of acetylcholine (ACh) were studied in perfused and intact superior cervical ganglia of cats. ACh was determined by bio-assay in ganglion extracts and in the venous effluent from ganglia perfused with fluid containing an anticholinesterase drug. Of the extractable ACh in a normal ganglion, about 85% is "depot ACh" available for release by nerve impulses. This must be located in the nerve endings; most of the remainder is in the intraganglionic portions of the preganglionic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
268
2

Year Published

1962
1962
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 541 publications
(303 citation statements)
references
References 22 publications
33
268
2
Order By: Relevance
“…They provide support for the general concept that the neurotransmitter used for synaptic signaling is drawn from a nonarbitrary RRP (Birks and MacIntosh, 1961;Elmqvist and Quastel, 1965) and for our particular model of RRP replenishment (Eq. 1).…”
Section: Stimulation Frequencysupporting
confidence: 63%
See 1 more Smart Citation
“…They provide support for the general concept that the neurotransmitter used for synaptic signaling is drawn from a nonarbitrary RRP (Birks and MacIntosh, 1961;Elmqvist and Quastel, 1965) and for our particular model of RRP replenishment (Eq. 1).…”
Section: Stimulation Frequencysupporting
confidence: 63%
“…Previous studies have primarily measured the time it takes for the RRP to refill during periods of rest, most finding that recovery from depletion takes at least several seconds (Birks and MacIntosh, 1961;Elmqvist and Quastel, 1965;Stevens and Tsujimoto, 1995;Rosenmund and Stevens, 1996;Wu and Borst, 1999). The residual calcium that is cleared slowly from synaptic terminals after bouts of intense activity has been shown to accelerate the replenishment process several-fold (Dittman and Regehr, 1998;Wesseling, 1998, 1999a;Wang and Kaczmarek, 1998).…”
mentioning
confidence: 99%
“…In a dose equimolar to that of atropine, benactyzine caused no significant change in the level of acetylcholine in the brain. Schueler (1961) has suggested that hemicholinium inhibits the synthesis of acetylcholine, and Birks & Macintosh (1961) have shown that, in the cat, the inhibition of synthesis of acetylcholine by hemicholinium leads to a decreased output of acetylcholine in the perfusate from the perfused superior cervical ganglion in situ.…”
Section: Resultsmentioning
confidence: 99%
“…Although it is not clear if the vesicular dynamics are the same at all synapses, our results show that the recruitment of more synapses does not lead to different dynamics. Early kinetic studies suggested the existence of multiple vesicular pools, since depression has 2-3 kinetic phases (Birks and MacIntosh 1961;Dittman and Regehr 1998;Kasai 1999), each taken to indicate the depletion of vesicles from the corresponding pool (Heinemann et al 1993;Horrigan and Bookman 1994;Oheim et al 1999;Parsons et al 1995). The fractional release can be estimated using 'tetanic rundown' (Christensen and Martin 1970), but this method is accurate only if the replenishment of the RRP during the rundown plays just a minimal role.…”
Section: Discussionmentioning
confidence: 99%
“…As the readily releasable pool (RRP) becomes depleted, its replenishment becomes a more important component of synaptic transmission (Birks and MacIntosh 1961;Larkman et al 1991). The replenishment rate, which influences the fast component of synaptic depression and determines the steady state level, is typically unknown.…”
Section: Introductionmentioning
confidence: 99%